Evaluation of genetic homogeneity of Jatropha curcas L. hybrid at an early stage of shoot bud formation from petioles using ISSR marker - Md. Nasir, Nor Anis Nadhirah; Anuar, Nurina; Zainuddin, Zarina; Yaakob, Zahira (Taylor & Francis Online, 2017)
Genetic homogeneity is known to be the most important prerequisite in the micropropagation of Jatropha curcas L. to produce true-to-type plants. The detection of genetic homogeneity in clonal micropropagation for elite plants at an early stage is required, to avoid any increase in variation in the next stage of micropropagation. The genetic homogeneity was assessed during shoot bud formation from petiole explants of J.curcas (P1 £ P3) hybrid with different concentrations of thidiazuron (TDZ) in a range of 0.5–4.0 mg/L using inter simple sequence repeat (ISSR) markers. Out of 23 ISSR primers, 16 primers produced clear, distinct and reproducible bands. A total of 96 bands, ranging in size from 100 to 1013 bp were generated. Based on the band data, a total of 94 bands were monomorphic (98%) and two bands were polymorphic (2%). All banding patterns from the shoot buds induced by 0.5, 1.0 and 2.0 mg/L TDZ were monomorphic, but 4.0 mg/L gave 2% polymorphism. These findings indicated that concentrations of 0.5, 1.0 and 2.0 mg/L TDZ did not trigger any somaclonal variation and could, therefore, be considered suitable for application in clonal micropropagation of J. curcas hybrid using petioles as explant material.